Impact of early childhood intervention programs on economic growth and equity - Urrutia, Miguel (IDB WashingtonUS, 1999)
Looks at the new consensus with respect to the need for early childhood intervention, and at quantifying the benefit/cost ratio of early child development interventions. Examines low cost versus costly integrated programmes